CERPEN PAK PUTU JONI, CERPEN KURSI RODA DAN CERPEN SINENGKAWONAN Karya I Gusti Putu Bawa Samar Gantang Analisis Struktur dan Nilai - Suryadi, I Wayan Beny (Humanis; Volume 3. No. 2. Mei 2013)
Pak Putu Joni Short Story, Short Story Wheelchairs, and a short story Sinengkawonan created by I Gusti Putu bawa Samar Gantang analyzed the structure and aims to transform and understand the value of the structural elements and values. Structural theory is used based on the Teeuw the dominant elements in a literary work. For value analysis based on the theory of the value delivered by Yudibrata, the value is the level of policy, goodness, and usability are owned by something. A value may be derived from a person's perception of something noble, humane, quality, and noble. Methods and techniques of research is divided into three phases, namely the provision of data by the method of repeated readings and interviews. Stage of data analysis used descriptive analytical method combined with formal methods and assisted with the values approach. Stage presentation of results of data analysis using formal and informal methods. The results obtained from this study, the unfolding structure Pak Putu Joni Short Story, Short Story Wheelchairs, and Short Story Sinengkawonan that there Incident, Chronology, People and characterizations, Background, Themes, and mandate that build these short stories. Disclosure of the values in the Short Story Pak Putu Joni, Wheelchairs Short Story, and Short Story Sinengkawonan and its relation to society that religious values, work ethic values, the value of love, the value of education and its relation to the reality of what happens in society.
Keywords: short stories, structure and value.